EXPERIMENTAL DETERMINATION OF DRYING KINETICS OF QUARTZ SAND IN A DRUM DRYER (American Journal of Technology and Applied Sciences, 2023)
The article provides information on the problems in the process of drying materials and the methods of reducing energy consumption for drying. A drum dryer and quartz sand taken from different mines were selected as the object of research, and the amount of quartz sand leaving the device was determined depending on the speed and temperature of the heat agent during the drying process. An empirical equation that determines the amount of material leaving the dryer is proposed.